Uma viagem ao encontro do tempo de alteridade no turismo : desmembrando horizontes epistemológicos a partir das contribuições de uma filosofia dialógica da linguagem do Círculo de Bakhtin - Bassinello, Patrícia Zaczuk (Universidade Federal de São Carlos, 2017)
In this passage we set out to offer our counterwords to the theoretical-methodological and conception senses of Tourism produced in the academic-scientific sphere, starting from the contributions of a dialogical philosophy of Bakhtin's Circle language. Encouraged to enrich, advance and broaden an epistemological and philosophical discussion that Tourism, as a field of studies, has been providing theoretical positions, we are betting first on building approximations and understandings about knowledge in Tourism from the dialogue with two renowned authors with international insertion in the area, who together are dedicated to studies that deal with epistemology and the theoretical approaches of Tourism. Assuming as a philosophical and methodological approach the perspective of Bakhtinian studies, we take as central sign materiality the statements of these authors, extracted from a work and articles frequently revisited by the national and international scientific community. The focus of the analysis of the excerpts taken as object is to study the discursive events that focused on the production of the senses by the authors. In this meeting we seek to highlight other possible meanings and ways to build knowledge through a collating movement and openness to the multiple relationships that make it possible to build understandings and new interpretations about our objects of study. We also realize that we can establish a movement of criticism of dialogic reason in tourism studies, through the road of otherness, as a construct and a more humane path for this area and a field of growing knowledge and scientific maturity.In this sense,, we get to meet the listening to the other word in Tourism and we are looking for build our narrative project for this area. We find another word in singular narratives of life, extracted from unofficial and scientific channels of the tourist discourse, that gave the opportunity to direct other fronts of understanding for Tourism and its practices, such as the time of otherness in Tourism, which is the available(unfunctional) time for the other as a meeting of historical and cultural alterities in the multiplicity of our singular and unique relations, in the lived experience. We also reinforce the existence of a tourist language which is and has been done in daily life too, in a living esthetic of daily life that spreads through the whole day and destiny and attractive tourist and that invades every experiential space, every unfinished language.The revolution proposed by the Bakhtin Circle, carried out by the listening to the other word and loving-kindness in all relations for a possible way of building another humanism, even in the case of Tourism, once in the heart of identity lies the beauty of Otherness. We believe that this journey made it possible to broaden the epistemological horizons of tourism through a dialogical movement of deconstruction of "identity masks" for the consolidation of more solidary and human realities in Tourism, thus re-signifying its practices.
A journey to meet the time of alterity in tourism : dismembering epistemological horizons from the contributions of a dialogical philosophy of the Bakhtin Circle language
Keywords: Tempo de alteridade; Linguagem; Turismo; Teoria dialógica; Círculo de Bakhtin; Time of alterity; Language; Tourism; Dialogical theory; Bakhtin circle; OUTROS